Nice white ladies the truth about white supremacy, our role in it, and how we can help dismantle it - Daniels, Jessie 1961- (New York City Seal Press, 2021)
"In Nice White Ladies Jessie Daniels addresses white women's complicity in racial discrimination in the US but also in their unique potential to resist and dismantle the white nationalism that threatens us all. Daniels is a white woman seeking to call in fellow white women to think together and act rather than simply call out and criticize. Ultimately, she shows how white women can be more than allies, but trusted accomplices in a shared mission to secure equality for all"--
Includes bibliographical references
Keywords: Women, White -- United States -- Attitudes; White supremacy movements -- United States; Racism -- United States; Social Justice -- United States; United States -- Race relations